PENERAPAN EDUKASI TENTANG RESIKO JATUH PADA LANSIA DENGAN MEDIA VIDEO - Sulistyowati, Endang; Isnugroho, Hernawan; Yunitasari, Pritta (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2024)
Elderly is a population group that tends to experience falls due to physical and cognitive changes that occur with age. This activity aims to increase the elderly and their families about the risk factors for falling and how to reduce these risks. The method used is by providing couseling and showing video demontrations on how to prevent and help fall in the elderly. The conclusion that can be drawn form this activity is that prevention and assistance at the risk of falling in the elderly which is done correctly can prevent complications due to falls.